The Use of Complementary and Alternative Medicine Supplements of Potential Concern during Breast Cancer Chemotherapy. (26th July 2016) - Sweet, Erin; Dowd, Fred; Zhou, May; Standish, Leanna J.; Andersen, M. Robyn
Abstract : Objective. While many Complementary and Alternative Medicines (CAM) are unlikely to interact negatively with conventional oncology treatment, some ingestible CAM substances have biological activities that may reduce the effectiveness of chemotherapy or radiation. This study surveyed women with breast cancer in order to document the extent to which women with breast cancer use these CAM substances of concern concurrently with conventional treatments. Methods. A total of 398 women completed a survey describing their use of CAM at various time points in their cancer treatment. This report focuses on a subsample of 250 women receiving chemotherapy or radiation who reported using specific one or more of several chemotherapies. Results. Of those participating, 104 (43.7%) of those receiving chemotherapy (n = 238 ) and 45 (32.3%) of those receiving radiation (139; 58.4% of all patients) reported using one or more CAM substances that could be cause for concern when taken concurrently. Conclusion. Research is needed to understand the real risks associated with CAM and conventional polypharmacy. If risks associated with CAM conventional polypharmacy use prove to be substantial then improved systems to assure all women get advice regarding herb and supplement use during breast cancer treatment appear to be needed.